Ultrahigh Detective Heterogeneous Photosensor Arrays with In‐Pixel Signal Boosting Capability for Large‐Area and Skin‐Compatible Electronics. Issue 16 (1st March 2016) - Kim, Jaehyun; Kim, Jaekyun; Jo, Sangho; Kang, Jingu; Jo, Jeong‐Wan; Lee, Myungwon; Moon, Juhyuk; Yang, Lin; Kim, Myung‐Gil; Kim, Yong‐Hoon; Park, Sung Kyu
Abstract : An ultra‐thin and large‐area skin‐compatible heterogeneous organic/metal‐oxide photosensor array is demonstrated which is capable of sensing and boosting signals with high detectivity and signal‐to‐noise ratio. For the realization of ultra‐flexible and high‐sensitive heterogeneous photosensor arrays on a polyimide substrate having organic sensor arrays and metal‐oxide boosting circuitry, solution‐processing and room‐temperature alternating photochemical conversion routes are applied.